Functional Modification of Fibrous PCL Scaffolds with Fusion Protein VEGF‐HGFI Enhanced Cellularization and Vascularization. Issue 18 (8th July 2016) - Zhao, Liqiang; Ma, Shaoyang; Pan, Yiwa; Zhang, Qiuying; Wang, Kai; Song, Dongmin; Wang, Xiangxiang; Feng, Guowei; Liu, Ruming; Xu, Haijin; Zhang, Jun; Qiao, Mingqiang; et al.
Abstract : The lack of efficient vascularization within frequently used poly(ε‐caprolactone) (PCL) scaffolds has hindered their application in tissue engineering. Hydrophobin HGFI, an amphiphilic protein, can form a self‐assembly layer on the surface of PCL scaffolds and convert their wettability. In this study, a fusion protein consisting of HGFI and vascular endothelial growth factor (VEGF) is prepared by Pichia pastoris expression system. Sodium dodecyl sulface‐polyacrylamide gel electrophoresis (SDS‐PAGE) and western blotting confirm that the VEGF‐HGFI is successfully isolated and purified. Transmission electron microscope and water contact angle measurement demonstrate that VEGF‐HGFI can form a self‐assembly layer with about 25 nm in thickness on electrospun PCL fibers and increase their hydrophilicity. VEGF‐HGFI modification can effectively enhance the adhesion, migration, and proliferation of human umbilical vein endothelial cells. Near‐infrared fluorescence imaging shows that the VEGF‐HGFI modification on PCL scaffolds can exist at least 21 d in vitro and at least 14 d in vivo. Bioluminescence imaging shows that VEGF‐HGFI can effectively activate vascular endothelial growth factor receptor 2 receptors. Subcutaneous implantation in mice and rats reveal that cellularization and vascularization are significantly improved in VEGF‐HGFI modified PCL scaffolds. These results suggest that VEGF‐HGFI is a useful molecule for functional modification of scaffolds to enhance cellularization and vascularization in tissue engineering. Abstract : A fusion protein consisting of hydrophobin HGFI and vascular endothelial growth factor (VEGF) is produced in this study. This fusion protein VEGF‐HGFI can form VEGF coating on electrospun poly (ε‐caprolactone) (PCL) fibers' surface by the self‐assembly of HGFI. Subcutaneous implantation results reveal that VEGF‐HGFI modification can enhance cellularization and vascularization within PCL scaffolds.